Correlation Between Brain-Derived Neurotrophic Factor and Cognitive Function in Older Adults - Effi Rohani Nuzul Sari; Fasihah Irfani Fitri; Aldy Safruddin Rambe; Taufik Ashar (Medicinski glasnik, 2025)
Aim: Brain Derived Neurotrophic Factor (BDNF) plays a crucial role in supporting neuronal survival, promoting neurogenesis, and enhancing synaptic plasticity, all of which are vital for cognitive health. Aim: of this study was to investigate the relationship between BDNF levels and cognitive impairment in the elderly population. Methods: This was a cross-sectional study involving older adults at a social service care. Cognitive function was assessed using the Montreal Cognitive Assessment-Indonesian Version (MoCA-INA). BDNF levels were measured in peripheral blood samples using the Enzyme-Linked Immunosorbent Assay. Results: Of the 88 participants (50 females 38 males) with a median age of 69.5 years, 71 (80.7%) had cognitive impairment. The median MoCA-INA score was 15.0. The most affected cognitive domain was abstraction, absolute number of patients 87 patients (98.9%). The mean BDNF level was 1.55 (±0.62) ng/mL with 50 (56.8%) patients having normal level. A weak positive correlation was found between BDNF level and performance in the visuospatial-executive (r= 0.232; p=0.029) and abstraction domains (r= 0.249; p=0.019). BDNF levels were significantly lower in those with cognitive impairment compared to those with normal cognitive function (p=0.029). Conclusion: A correlation between BDNF levels and cognitive function, particularly in the visuospatial-executive and abstraction domains, highlighting the potential role of BDNF in cognitive decline in aging.
Keywords: Aging; biomarkers; cognition; Memory; Nerve Growth Factors